1996
DOI: 10.1002/art.1780391211
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of sulfasalazine and placebo in the treatment of reactive arthritis (Reiter's syndrome). A department of veterans affairs cooperative study

Abstract: Objective. To determine whether sulfasalazine (SSZ) at a dosage of 2,000 mglday is effective in the treatment of reactive arthritis (ReA) that has been unresponsive to nonsteroidal antiinflammatory drug (NSAID) therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
52
0
7

Year Published

1997
1997
2006
2006

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(60 citation statements)
references
References 7 publications
1
52
0
7
Order By: Relevance
“…No significant adverse events were reported (139,207). A large multicenter study conducted by the Department of Veterans' Affairs in patients with a chronic mean ReA duration of 10 years and unresponsive to conventional therapy demonstrated that sulfasalazine (2 g/day) is well tolerated and effective in treating ReA (34). A reanalysis of the same study published by the same study group showed different responses to sulfasalazine in patients with axial or peripheral involvement (33).…”
Section: Pharmacologic Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…No significant adverse events were reported (139,207). A large multicenter study conducted by the Department of Veterans' Affairs in patients with a chronic mean ReA duration of 10 years and unresponsive to conventional therapy demonstrated that sulfasalazine (2 g/day) is well tolerated and effective in treating ReA (34). A reanalysis of the same study published by the same study group showed different responses to sulfasalazine in patients with axial or peripheral involvement (33).…”
Section: Pharmacologic Approachmentioning
confidence: 99%
“…Depending on the triggering infection and on the follow-up time, chronic arthritis is observed in 2 to 18% of patients, sacroiliitis is observed in 14 to 49%, and AS is observed in 12 to 26% (91,117,200). In one of the earliest studies of ReA, chronic disability was found in 40 of 100 persons who were available for reexamination 25 years after onset of disease (34).…”
Section: Coursementioning
confidence: 99%
“…However, a substantial proportion of patients (ϳ20%) experience a chronic course that continues longer than 12 months (8,9). Currently, patients are treated symptomatically with nonsteroidal antiinflammatory drugs (NSAIDs) or, in severe cases, with steroids, and those with chronic courses are treated with second-line drugs, such as sulfasalazine, which have been shown to be effective (10). To shorten self-limited courses and to treat chronic cases more effectively, a better and possibly curative treatment is needed.…”
mentioning
confidence: 99%
“…Hier hat sich SSZ (2 bis max. 3 g/Tag; [7]) bewährt. Trotz unzureichender Studienlage kommen auch andere DMARDs, insbesondere MTX, zum Einsatz.…”
Section: Immunsuppressive Therapieunclassified